Addressing Frequent Issues of Home Enteral Nutrition Patients. (11th February 2019) - Johnson, Teresa W.; RN, Sara Seegmiller; Epp, Lisa; Mundi, Manpreet S.
Abstract: The home enteral nutrition (HEN) population is a medically diverse group whose number has increased substantially in recent decades. Although medically stable compared with acute care patients requiring nutrition support, HEN population needs are unique and require a team approach to manage nutrition. Frequently encountered issues by the HEN team include mechanical issues of the tube site, gastrointestinal and metabolic problems, and patient preferences regarding tube weaning, formula selection, and compliance. A thorough search of the published literature on how to manage these issues was conducted using scientific healthcare databases with the following inclusion criteria: English only, last 10 years, and reviews and clinical trials. Where appropriate, references from the retrieved articles were hand‐searched for relevant articles older than 10 years and cited in this review. The purpose of this review is to provide the HEN team with strategies to address the top issues of home enteral feeding.